Theory-Practice Gaps in Developing Critical Thinking: Insights from A Pedagogical Study in Omani Context - Moosa Ahmed Ali Sulaiman; Suyansah Swanto; Wardatul Akmam Din (2018)
With this premise as a backdrop that effective use of Socratic questioning in instructional practices is of vital importance in English as a forging language (EFL) classrooms, this study was undertaken to investigate application of Omani knowledge of Socratic questioning (SQ) on students’ critical thinking (CT) in post basic schools. This study investigates the application of Omani EFL of SQ on students’ CT in post basic schools. The present study attempts to a) ascertain whether there is any statistically significant difference between mean scores of those who are taught through SQ and those obtained by students who are taught CT skills in a normal setting. b) identify SQ strategies that helped to develop the students’ CT skills. An experimental research design was implemented. There were 60 students participated in this study 30 students in each group. The Mixed method procedures and data analysis showed that, a) significant differences between mean scores of those who were taught CT through SQ and those who were taught CT skills in a normal setting, c) there is clear evidence that students in the experimental group had evolved effective CT strategies during the intervention phase.